Pengaruh Critical thinking dan Open-mindedness terhadap Pemahaman Konsep Pembelajaran Mahasiswa Semester VII (Studi pada Mahasiswa Peserta PPL di STIT Raden Wijaya Mojokerto) - Anwar Sholihin (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
Education also fosters cultural innovation, because it can stimulate intellectual inquiry and foster critical thinking which is the basis for developing new ideas. The purpose of this paper is 1). Identifying critical thinking and open-mindedness simultaneously influence the understanding of the seventh semester student learning concepts; 2). Identifying critical thinking and open-mindedness partially influence the understanding of the seventh semester student learning concepts; 3). Identify variables that predominantly influence the level of understanding of the seventh semester student learning concepts. The results showed that Critical thinking and Open-mindedness had a simultaneous effect on understanding the learning concepts of semester VII students, namely X1 (Critical thinking) and X2 (Open-mindedness). The calculated F value was greater than the F table value (4,391> 3,35). . Open-mindedness Critical thinking and prices have a partial effect on the t-value of understanding the seventh semester student learning concept (3.45> 2.055) with a significance level of less than 0.05 0.008 and X2 (Open-mindedness) variable greater than t table (8.561> 2,055) with a significance level below 0.05 which is 0.002. And the most dominant variable influencing the understanding of the seventh semester student learning concept is Open-mindedness from the SPSS results which shows between X1 (Critical thinking) and X2 (Open-mindedness) variables obtained in X1 variable, Pearson correlation 0.381 <Pearson X2 correlation 0.081 This means that the Open-mindedness X2 variable has more influence on understanding the seventh semester student learning concepts.